Experimental investigation on flexural behaviour of composite PVC encased macro-synthetic fibre reinforced concrete walls. (1st March 2021) - Far, Harry; Nejadi, Shami
Highlights: Fifteen composite PVC encased concrete wall specimens were tested at UTS Tech Lab. For flexural testing, three-point bending test on a three-metre span was chosen. Using BarChip 48 leads to 43.5% strength improvement and 25% stiffness enhancement. BarChip 48 walls exhibit 2.4 % more capacity than conventional reinforced walls. BarChip 48 walls without rebars are suitable for sway-prevented structures. Abstract: Composite PVC encased concrete walls provide substantial advantages in terms of structural strength and durability enhancement, ultraviolet radiation and pest infestation resistance, design flexibility, ease of construction and excellent resistance to impact. In this study, the effects of using macro-synthetic fibre reinforced concrete on flexural behaviour of composite PVC encased walls in comparison with composite PVC encased walls filled with conventional plain concrete and reinforced concrete have been experimentally investigated. Fifteen composite PVC encased concrete wall specimens were cast and tested using three-point bending test. Based on the load-deflection curves resulting from the three-point bending tests, flexural parameters including ultimate loads, ultimate flexural strengths, stiffness and flexural rigidity values for cracked and uncracked conditions were determined for three different cases including i) test specimens filled with plain concrete, ii) test specimens filled with macro-synthetic fibre reinforced concrete, and iii) test specimens filled with reinforced concrete. The determined parameters as well as the measured load-deflection curves for the three cases were compared and the final findings have been discussed. Based on this study, it has become apparent that using BarChip 48 macro-synthetic fibre reinforced concrete in composite PVC encased walls instead of plain concrete can lead to 43.5% flexural strength improvement and 25% stiffness enhancement at the age of 28 days. Based on the experimental measurements and theoretical comparison in this study, it has been concluded that composite PVC encased walls filled with BarChip 48 macro-synthetic fibre reinforced concrete, without steel reinforcement, are deemed suitable for sway-prevented structures such as retaining walls. If using steel reinforcement in composite PVC encased retaining walls is not an option due to high-risk of steel corrosion in harsh environment; it is highly recommended that the retaining walls to be filled with macro-synthetic fibre reinforced concrete instead of plain concrete to ensure the safety and structural integrity of this type of sway-prevented structures.